Temporal patterns of breeding and recruitment in Nerophis lumbriciformis (Pisces; Syngnathidae) related to seawater temperatures - Monteiro, Nuno Miguel (2012)
The breeding season of Nerophis lumbriciformis, a cold water pipefish, was positively correlated with seawater temperatures <15 5 C, whilst recruitment occurred at the end of the upwelling season, when seawater temperature attained its maximum values. The observed alterations in seawater temperatures, with steady year-round increases, and the consequent alteration of the upwelling regime, may have dramatic consequences in the maintenance of N. lumbriciformis populations, by reducing the breeding period and simultaneously contributing to the transport of pelagic larvae northwards due to specific sea currents that occur outside the upwelling season.